ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN/KOTA DI KAWASAN SARBAGITA PROVINSI BALI - Yudastini, Ni Putu Andari; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p10, 2023)
Sarbagita area is a metropolitan area in Bali province. Regional Original Income between Regencies/Cities in the Sarbagita Area is still experiencing a shock. Regional Original Revenue can be influenced by several factors, including GRDP Per Capita, Total Population, and Number of Tourist Visits. The purpose of this study was to analyze the effect of GRDP per capita, total population, and the number of tourist visits simultaneously and partially on Regional Original Income. The number of observations in the study were 60 observations. The data were obtained from the Central Statistics Agency for the Province of Bali, the Central Statistics Agency for each Regency/City in the Sarbagita Area and the Tourism Office of the Province of Bali. The analytical technique used in this study is Multiple Linear Regression with the help of the E-views 9 analysis tool. The results show that simultaneously GRDP per capita, number of residents and number of visits have an effect on local revenue. partially GRDP per capita, population, and number of tourist visits have a positive and significant impact on Regency/City Original Revenue in the Sarbagita Region.